Identification of DNA-Microsatellite Markers for the Characterization of Somatic Embryos in Quercus suber - Gómez-Garay, Arancha; Bueno, Ángeles; Pintos, Beatriz (Microsatellites SE - 8, 2013)
Nuclear DNA-microsatellite markers led the possibility to characterize individually both Quercus suber trees and somatic embryos. The genotype inferred by SSR markers opens the possibility to obtain a fingerprint for clonal lines identification. Furthermore, allow to infer the origin of somatic embryos from haploid cells (microspores) or from diploid tissues. Using few SSR markers from other Quercus species and an automatic system based in fluorescence, it is possible to obtain a high discrimination power between genotypes. This method is sufficient to assign tissues to an individual tree with high statistical certainty. Nevertheless, it is necessary to take care to select the adequate DNA extraction method to avoid PCR inhibitors present in diverse Q. suber tissues.
The following values have no corresponding Zotero field: periodical: Microsatellites SE - 8 electronic-resource-num: 10.1007/978-1-62703-389-3_8
Keywords: Clonal lines; Doubled haploid; Dyes; Fingerprint; Germplasm; Haploid

Oak somatic and gametic embryos maturation is affected by charcoal and specific aminoacids mixture - Pintos, Beatriz; Manzanera, Jose a; Bueno, M. Angeles (Annals of Forest Science, 2010)
• Development of both somatic and gametic embryogenesis has many applications in clonal forestry and genetic improvement, for instance as mass-propagation of genetically improved plants and production of pure lines through doubled-haploid plant regeneration from gametic embryos. • The goal of this work was to improve growth, maturation and plantlet regeneration of cork oak (Quercus suber L.) embryos from both somatic and gametic origin. • Activated charcoal promoted a signiﬁcant increase in growth in terms of relative size and weight of both somatic and doubled-haploid embryos, as well as a more eﬃcient control of secondary somatic embryogenesis during development. A signiﬁcant interaction was also observed with amino acid nutrition. While some amino acids (i.e., glutamine, arginine or asparagine) did not show signiﬁcant diﬀerences with the controls, a mixture of these three amino acids or gamma amino butyric acid stimulated embryo growth. The highest survival rate during acclimation of plantlets from both somatic and doubled-haploid origin was obtained when the embryos had been previously cultured on basal medium with 3% sucrose and 1% activated charcoal for two months at 4 ◦ C and germinated on medium supplemented with 6-benzylaminopurine and indole-3-butyric acid. • We obtained more than 900 cork oak plantlets acclimated from several embryogenic lines, with a high survival rate, demonstrating that this methodology is applicable for large scale plantlet production. We also report the ﬁrst regeneration of doubled-haploid plantlets in cork oak.
Keywords: activated charcoal; amino acids; Cork oak; gametic embryo; plantlet acclimation

Proteomic analysis from haploid and diploid embryos of Quercus suber L. identifies qualitative and quantitative differential expression patterns. - Gómez, Aranzazu; López, Juan Antonio; Pintos, Beatriz; Camafeita, Emilio; Bueno, Ma Angeles (Proteomics, 2009)
Quercus suber L. is a Mediterranean forest species with ecological, social and economic value. Clonal propagation of Q. suber elite trees has been successfully obtained from in vitro-derived somatic and gametic embryos. These clonal lines play a main role in breeding and genetic studies of Q. suber. To aid in unravelling diverse genetic and biological unknowns, a proteomic approach is proposed. The proteomic analysis of Q. suber somatic and gametic in vitro culture-derived embryos, based on DIGE and MALDI-MS, has produced for the first time proteomic data on this species. Seventeen differentially expressed proteins have been identified which display significantly altered levels between gametic and somatic embryos. These proteins are involved in a variety of cellular processes, most of which had been neither previously associated with embryo development nor identified in the genus Quercus. Some of these proteins are involved in stress and pollen development and others play a role in the metabolism of tannins and phenylpropanoids, which represent two of the major pathways for the synthesis of cork chemical components. Furthermore, the augmented expression levels found for specific proteins are probably related to the homozygous state of a doubled-haploid sample. Proteins involved in synthesis of cork components can be detected at such early stages of development, showing the potential of the method to be useful in searching for biomarkers related to cork quality.
Keywords: cluster analysis; Cork oak; Diploidy; Electrophoresis; Embryonic Development; flow cytometry; Gametic embryogenesis; Gel; Haploid and diploid embryos; Haploidy; Plant Proteins; Plant Proteins: analysis; Plant Proteins: biosynthesis; Plant Proteins: genetics; Plant proteomics; Ploidies; Ploidy level; Principal component analysis; Proteomics; Proteomics: methods; Quercus; Quercus suber L.; Quercus: chemistry; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Seeds: genetics; Seeds: metabolism; Two-Dimensional; Up-Regulation

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S.; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C. (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
The following values have no corresponding Zotero field: accession-num: 15346811
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure